An Efficient Computational Risk Prediction Model of Heart Diseases Based on Dual-Stage Stacked Machine Learning Approaches - T Uday Kiran; Kundam Madhusudhan Reddy; Molagavalli Vamsi; Kamsali Sai Kiran; K. Kumaraswamy (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Cardiovascular diseases (CVDs) continue to be a prominent cause of global mortality, necessitating the development of effective risk prediction models to combat the rise in heart disease (HD) mortality rates. This work presents an overdue-stage stacked machine learning (ML) based computational risk prediction model for cardiac disorders. Leveraging a dataset that includes eleven significant characteristics from 1190 patients from five distinct sources, five ML classifiers are utilized to create the initial prediction model. To ensure robustness and generalizability, the classifiers are cross-validated ten times. The model performance is optimized by employing two hyper parameter tuning approaches: Randomized Search CV and Grid Search CV. These methods aim to find the optimal estimator values. The highest- performing models, specifically Random Forest, Extreme Gradient Boost, and Decision Tree undergo additional refinement using a stacking ensemble technique. The stacking model, which leverages the capabilities of the three models, attains a remarkable accuracy rate of 96%, a recall value of 0.98, and a ROC-AUC score of 0.96. Notably, the rate of false- negative results is below 1%, demonstrating a high level of accuracy and a non-over fitted model. To evaluate the model’s stability and repeatability, a comparable dataset consisting of 1000 occurrences is employed. The model consistently achieves an accuracy of 96.88%under identical experimental settings. This highlights the strength and dependability of the suggested computer model for predicting the risk of cardiac illnesses. The outcomes indicate that employing this two-step stacking ML method shows potential for prompt and precise diagnosis, hence aiding the worldwide endeavor to decrease fatalities caused by heart disease.
Keywords: cardiovascular disease (CVD); extreme gradient boost (XGB); hyper-parameter tuning; heart disease; random forest classifier; stacking ensemble technique